Knowledge management for disaster response: A proposed framework - Dorasamy, Magiswary; Jennex, Murray E.; Raman, Murali; Kaliannan, Maniam (2008)
Knowledge management encompasses a wide range of disciplines. Most organizations face difficult challenges in managing knowledge for emergency response, but it is crucial for response effectiveness that such challenges be overcome.Organizational members must share the knowledge needed to plan for emergencies. They also must be able during an emergency to access relevant plans and communicate about their responses to it.In this paper we purport the idea that knowledge management systems allow more effective and timely disaster management efforts.We present our idea based on our experience in working with knowledge management systems to support emergency preparedness initiatives in North America. We propose a framework that can be used by local researchers and practitioners to better understand the influence of knowledge management on disaster management.